Etude Eco-Dendrométrique Du Dépérissement Du Cèdre De l’Atlas Dans Le Parc National De Theniet El Had “Algérie” - Lamine, Taleb Mohamed; M’hamed, Maatoug; Blel, Azouzi; Mohamed, Zedek; Benchabane, Hellal (European Scientific Journal, ESJ, 2016)
This study aims to search the relationship between the decline of the Atlas cedar and the eco-dendrometrique factors in the National Park of Theniet El Had located in the north-west of Algeria. This study takes place throughout 30 circular plots of 1.000m2 area in which, a dendrometric measures and ecological data are taken in addition to descriptive data for Atlas cedar trees. The descriptive data shows that 34% of inventoried Atlas cedar have damaged leaves and 30% have more then 25% of their crowns damaged. The analysis of variance shows that there is no relationship between the rate of the Atlas cedar decline ant the ecological factors, components of the soil and dendrometric parameters except for the average circumference witch is influenced by the competition between trees. Therefor, a particular management plan for the regulation of competition is a necessity for this park.